Regulator of G protein signaling 12 drives inflammatory arthritis by activating synovial fibroblasts through MYCBP2/KIF2A signaling - Gongsheng Yuan; Shu-ting Yang; Shuying Yang (Elsevier, 2023)
Synovial fibroblasts are the active and aggressive drivers in the progression of arthritis, but the cellular and molecular mechanisms remain unknown. Here, our results showed that regulator of G protein signaling 12 (RGS12) maintained ciliogenesis in synovial fibroblasts, which is critical for the development of inflammatory arthritis. Deletion of RGS12 led to a significant decrease in ciliogenesis, adhesion, migration, and secretion of synovial fibroblasts. Mechanistically, RGS12 overexpression in synovial fibroblasts increased the length and number of cilia but decreased the protein level of kinesin family member 2A (KIF2A). The results of LC-MS analyses showed that RGS12 interacted with MYC binding protein 2 to enhance its ubiquitination activity, through which the KIF2A protein was degraded in synovial fibroblasts. Moreover, overexpression of KIF2A blocked the increases in cilia length and number. Mice with RGS12 deficiency or treatment of RGS12 shRNA nanoparticles significantly decreased the clinical score, paw swelling, synovitis, and cartilage destruction during inflammatory arthritis by inhibiting the activation of synovial fibroblasts. Therefore, this study provides evidence that RGS12 activates synovial fibroblasts' pathological function via promoting MCYBP2-mediated degradation of KIF2A and ciliogenesis. Our data suggest that RGS12 may be a potential drug target for the treatment of inflammatory arthritis.